Shape-Based Matching: Application of Edge Detection Using Harris Point - Sulaiman , Marizan; Mohd Shah, Hairol Nizam (2011)
This paper presents a seqence of object rcognition algorithm using shape-based matching that mainly focused on image recognition, image segmentation and flexible Region of Interest.